Association of inpatient postpartum recovery with patient-reported outcome measures following hospital discharge: a prospective cohort study - Carrie M. Stump; Feyce M. Peralta; Pervez Sultan; Michael E. Holland; Nevert Badreldin; Lelesse C. Shepard; Robert J. McCarthy (BMC, 2024)
Abstract Background The relationship between the quality of inpatient versus outpatient obstetric postpartum recovery is under-explored. We examined the association between inpatient reported quality of recovery with outpatient global recovery, pain severity, pain interference, anxiety, and depression screening scores postpartum. Methods We conducted a multicenter observational cohort study of women in labor who underwent vaginal, operative vaginal, or intrapartum cesarean birth. Subjects completed baseline assessments of pain, social support, anxiety, and depression in early labor. We assessed the Obstetric Quality of Recovery-10 (ObsQoR-10) on the day of discharge and the ObsQoR-10, Global Health Scale (GHVAS; 0-100), Brief Pain Inventory (BPI), and the Edinburgh Postnatal Depression Scale (EPDS) on postpartum day seven. We hypothesized that the ObsQoR-10 scores at discharge would be useful in predicting postpartum day seven measures of recovery and postpartum depression screening scores. Results We consented 558 subjects, 551/558(98%) completed baseline assessments, 400/551(72%) completed the ObsQoR-10 tool, and 344/551(62%) completed an EPDS assessment. Median (1st, 3rd quartile) ObsQoR-10 scores were 78 (63, 90) at discharge and 85 (68,93) on postpartum day seven, (difference of 7 [99% CI 2 to 13], P < 0.001). GHVAS on postpartum day seven identified 204/344 (59%) of subjects with good recovery. An ObsQoR-10 score of > 86 at discharge had a RR of 1.5 [95% CI 1.2 to 1.8], P < 0.001 for good recovery at postpartum day seven, the EPDS identified 20/344 (5.8%) respondents with a score ≥ 13 on postpartum day seven. The area under the curve between the ObsQoR-10 at discharge with an EPDS ≥ 13 was 0.74 (99% CI 0.61 to 0.86, P < 0.001). The RR for an EPDS ≥ 13 on postpartum day seven with an ObsQoR-10 < 77 on the day of discharge was 7.8 (95% CI 1.8 to 33.8; P = 0.001). Conclusions ObsQoR-10 scores at discharge and postpartum day seven demonstrated increased obstetric recovery in the post-discharge period. The observed association between the ObsQoR-10 and the EPDS, suggests that the ObsQoR-10 might facilitate identification of women at increased risk of postpartum anxiety or depression. Identification of high-risk women at discharge may allow early interventions to reduce morbidity secondary to postpartum depression.